Answer:
a = -10
r = 4/5
Explanation:
geometric progression
formula
nth term = ar^n
a1 -a2 = 2
a(1-r)= 2
(1-r) = 2/a
sum of infinity ratio
a/(1-r) = 50
a = 50(1-r)
replace the value of (1-r) with 2/a
a = 50(2/a)
a = 100/a
a^2 = 100
a =
![√(100)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lj7jr15p8ds22ttux5vzbrrpqtzk3e8mjw.png)
a = ± 10
finding r
a(1-r)= 2
10(1-r) = 2
1-r = 2/10
1 - r = 1/5
1 + 1/5 = r
r = 4/5
making the sequence
10*4/5 = 8
10 , 8 , 32/5......
since it states that the second term exceeds by two... this means that the second term has to be greater than the first
Hence:
a = -10
meaning the sequence becomes:
-10 , -8 , -32/5
a = -10
r = 4/5